THE ROLE OF REFLECTIVE LISTENING IN STRENGTHENING EMOTIONAL BOND BETWEEN PARENTS AND CHILDREN (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the psychological essence and practical significance of the reflective listening method in strengthening the emotional bond between parents and children. Reflective listening is not merely the act of hearing words but a process of paying active and empathetic attention to the speaker’s emotions, feelings, and inner state. The research highlights how this method enhances mutual understanding, empathy, and trust within family communication. Moreover, the article analyzes the role of reflective listening in developing emotional intelligence, reducing stress levels, and fostering children’s ability to express their thoughts and emotions clearly. The study holds theoretical and practical value for professionals in family and child psychology.